Natural capitalism: the next industrial revolution - "Hawken, Paul" (London, 2002)
"'There's a new book out I commend to you called Natural Capitalism... This is a huge deal' President Clinton; 'An analysis of how capitalism would work if the world's "natural capital" were properly valued, resulting in a drastic reduction in resource use by industrialised countries' The Financial Times; 'A powerful, visionary statement by three of the world's leading consultants on the greening of business' The Times Higher Education Supplement; 'If any book can be said to usher in a hopeful new age, it's this' Jonathon Porritt, Director, Forum for the Future; 'Leaves every reader with the hope that the old battle between business and the environment can reach a peaceful and constructive conclusion' Frances Cairncross, The Economist; 'The whole concept of natural capital manages to be both pragmatic and idealistic which, in my book, adds up to inspirational' Anita Roddick, The Body Shop International; 'This is smart, strategic thinking' The Independent; 'Includes a wealth of real examples... The authors provide a boldly practical way forward' The Times; 'Points the way to a world where the profit motive and social responsibility march hand in hand' John Quelch, Dean, London Business School"
Keywords: Capitalism